A Clinical Assessment on the Efficacy of the Anterior and Middle Superior Alveolar Nerve Block Technique During Extraction of Maxillary Teeth - Faiz A Ayoob Al Sultan (University of Mosul, College of Dentistry, 2009)
Aims: A clinical evaluation on a recently introduced technique of anesthesia for maxillary teeth namelythe Anterior and Middle Superior alveolar nerve block compared with the conventional infiltrationtechnique for extraction of upper anterior and premolar teeth. Materials and methods: In the first partof the study, testing of pulpal anesthesia were performed after administering this technique for teethfrom upper central incisor to upper second premolar. The sample chosen for the second part of thestudy included 60 subjects of different ages and genders. The patients were divided randomly into twogroups: control group to whom the conventional supraperiosteal injection technique was administeredand the trial group to whom the anterior and middle superior alveolar nerve block technique was administered.In both groups, extraction was carried out. Results: The result of this study indicated thesuccess of achieving pulpal anesthesia after AMSA injection for teeth from the upper canine to the uppersecond premolar with no significant difference noticed between AMSA and control group in regardingto pain score levels after extraction of these teeth. Conclusions: This new technique could beused as a good alternative and or supplementary to the infiltration technique for anesthetizing maxillaryanterior and premolar teeth using a conventional dental syringe.